2017
DOI: 10.1111/ecoj.12366
|View full text |Cite
|
Sign up to set email alerts
|

Time Aggregation and State Dependence in Welfare Receipt

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…Consequently, the MSD models provide better within-sample predictions than do the DBR models. Consistent with recent literature (e.g., Bhuller et al 2017), we conclude that the standard dynamic binary response model is unacceptably restrictive in this context.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consequently, the MSD models provide better within-sample predictions than do the DBR models. Consistent with recent literature (e.g., Bhuller et al 2017), we conclude that the standard dynamic binary response model is unacceptably restrictive in this context.…”
Section: Introductionsupporting
confidence: 87%
“…To the best of our knowledge, the relationship between the DBR and MSD models has not been formally recognized, and very few studies have discussed the implications of the DBR models for transition probabilities and spell durations. Cappellari et al (2007) compared a duration and a Markov model for employment transitions, and Bhuller et al (2017) analyzed the adequacy of first-order dynamic binary response models against more general models that allow for duration and occurrence dependence. Gørgens and Hyslop (2018) showed that the DBR and MSD approaches are equivalent in a nonparametric context, and that nonparametric DBR models of order r ≤ 2 are nested within a simple MSD model.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address this issue Section 6 describes the components of income, which are attributable to the changes in income and poverty status between t − 1 and t. 16 An exception here is Biewen (2009). 17 Bhuller et al (2016) using Norwegian administrative using monthly micro-level data show that the conditional Markov property has implications for the aggregation of a dynamic processes over time. Their findings show the estimated state dependence is affected time aggregation bias if the conditional Markov assumption is violated, nonetheless they find even more complex higher-order structures are unable to satisfactorily account for the true data-generating process.…”
Section: Poverty Dynamics Among Older Individuals In the Uk 513mentioning
confidence: 99%
“…One reason is that employers often interpret long unemployment durations as a significant negative signal (see e.g. Kroft et al, 2013;Bhuller et al, 2017). If this is the case, such re-integration policies would be ineffective on average.…”
Section: Introductionmentioning
confidence: 99%